Visiting a Sufi Shaykh: A Contemporary Experience of Religious Pilgrimage - Makhabbad Maltabarova (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
Modern experience of spiritual search has mixed up all the colors of the religious domain. It is no longer a strict definition of what the term pilgrimage implies. There is a growing number of seemingly secular places visited by both members of traditional religious institutions and New Age movements. However, the Western culture of pilgrimage is still recognized as individual and not accepting religious elements as such. Using reliable sociological approaches and the ethnographical material, the present article challenges this assumption and seeks to create a more productive discussion on the topic. For this, it examines the Naqshbandi Haqqani Sufi community of Lefke (Cyprus), a place of pilgrimage for Muslims, non-Muslims, Europeans, Americans—all motivated by the goal of visiting a Sufi shaykh. The article analyzes the pilgrimage to Lefke by means of John Urry’s three bases of co-presence and illustrates how the Islamic vocabulary of pilgrimage has also changed in adaptation to the new realities of the post-secular world. As a result, it is argued that Sufism, with its historically proven ability to combine the individual and collective spheres of religious life, can provide a useful framework for understanding the contemporary pilgrimage phenomenon.